ACTUAL PROBLEMS OF TEACHING THE RUSSIAN LANGUAGE AND LITERATURE - Zoirova Firuza Uktamovna (Bright Mind Publishing, 2025)
Actual problems of teaching the Russian language and literature include several key aspects that require careful consideration. Firstly, these are challenges associated with a change in educational standards and programs, as well as the need to update teaching methods oriented to new requirements of society and technological achievements. An important aspect is also an improvement in the level of language training of students, especially in the context of the modern school system, where attention is paid not only by academic knowledge, but also by the development of critical thinking, creativity and sociability. Among the problems we include a shortage of qualified personnel, as well as a decrease in students' interest in subjects of the humanitarian cycle. An important role is also played by the introduction of new technologies and electronic resources in the learning process, which requires teachers not only skills in working with modern methods, but also the ability to adapt traditional approaches to new conditions. The aim of this work is to analyze the existing problems of teaching the Russian language and literature and the proposals of possible ways to solve them aimed at improving the quality of education and developing interest in students in these important disciplines.
Keywords: Teaching the Russian language, literature, educational standards, teaching methods, critical thinking, qualified personnel, technologies in training, electronic resources, humanitarian disciplines, students' interest, and quality of education.